A modified hybrid silsesquioxane/histidine composite for copper and zinc adsorption and it behavior in the electro-oxidation of ascorbic acid - Franco, Fernanda dos Santos [UNESP]; Fernandes, Daniela Silvestrini [UNESP]; Do Carmo, Devaney Ribeiro [UNESP] (Elsevier B.V., 2020)
Octa-(3-chloropropryl)silsesquioxane was chemically modified with histidine (SSQ-H) and characterized by spectroscopy in the infrared region (FT-IR), X-ray diffraction (XRD), X-ray Dispersive Energy Spectroscopy (EDX), Scanning Electron Microscopy (SEM). The analytical properties of SSQ-H were tested regarding of Cu2+ and Zn2+ adsorption and as an electrochemical sensor for the detection of ascorbic acid. The metal sorption results indicate that maximum amount of Cu2+ and Zn2+ adsorbed (Nf(max)) were 1.58 x 10(-3) and 5.67 x 10(-4) mol g(-1), respectively. After Cu2+ and Zn2+ ion adsorption and interaction with potassium hexacyanoferrate (III), the investigated materials displayed electroactivity for ascorbic acid detection. The anodic peak currents responses of a graphite paste electrode containing CuHCFSSQ-H presented a linear response in the concentration range of 4.0 x 10(-4) to 4.0 x 10(-3) mol L-1 for ascorbic acid detection. The limit of detection was of 2.99 x 10(-4) mol L-1, with an amperometric sensitivity of 1.69 mu A/mol L-1. The intensity of the anodic peak currents of the graphite paste electrode containing ZnHCFSSQ-H in the concentration range of 9.0 x 10(-5) to 9.0 x 10(-4) mol L-1 also displayed a linear response. The limit of detection was of 6.76 x 10(-5) mol L-1, with an amperometric sensitivity of 0.0206 A/mol L-1.
Keywords: Chemical synthesis; Infrared spectroscopy; X-ray diffraction; Electrochemical properties; Surface properties